Kontribusi Religiusitas terhadap Perilaku Prososial Guru Sekolah Inklusi Berbasis Islam - Faza Dinan Hanifah; Stephani Raihana Hamdan (Jurnal Psikologi Islam dan Budaya, 2021)
The purpose of this study was to find the contribution of religiosity to prosocial behavior on teacher inclusion. This study is a causality study with the respondent of 74 teachers. The measuring instrument used was CRS-15 (The Centrality of Religiosity Scale) adapted by Wardhani (2015) to measure religiosity and The Prosocialness Scale for Adults by Caprara (2005) and adapted by a researcher to measure prosocial. The results showed that there is a significant correlation between religiosity and prosocial. Religiosity contributes 40.7% to the prosocial behavior.